Successful Use of a Multidisciplinary Approach to Treat a Perforated Duodenal Malignant Lymphoma in an Elderly Patient - Tomoko Takagishi; Yuta Niimi; Goshi Matsuki; Shinta Nagano; Junsuke Hinami; Masaaki Kajiwara; Kiyoshi Kaneko; Yoshihiro Kubota; Osamu Nakai (Case Reports in Oncological Medicine)
Treatment of duodenal malignant lymphoma is difficult due to life-threatening complications such as intestinal obstruction, perforation, and pancreatitis. Thus, multidisciplinary procedures are required alongside surgical intervention. Contrast abdominal CT images of a 75-year-old female suffering from vomiting revealed thickening of the duodenal wall (from the second to third segment). Gastrojejunostomy and biopsy identified the tumor as diffuse large B-cell lymphoma. A diagnosis of stage II duodenal lymphoma was made. The lymphoma continued to grow, resulting in jaundice and intestinal perforation, which was first treated with two cycles of rituximab and antibiotics. Thereafter, less intensive chemotherapy (two cycles each of R-mini-CHP, CHP, and R-CHOP) was administered, which led to significant improvement upon assessment by PET-CT. Residual lymphoma was treated with consolidation radiotherapy (50 Gy in 25 fractions) over 5 weeks after chemotherapy. The patient attained a complete response and has been disease-free for more than 4 years. Thus, duodenal perforated lymphoma can be treated successfully using a multidisciplinary approach that combines surgery, immunochemotherapy, and radiation therapy.